KELAYAKAN DAN KEADILAN DALAM PENETAPAN UPAH NELAYAN KAPAL PUKAT LANGGAR KUALA LANGSA DITINJAU DARI PERSPEKTIF ETIKA BISNIS ISLAM - junaidi junaidi (IAIN Langsa, 2021)
Wages are a form of income as a reward given by the owner of the boat to fishermen for services that have been provided. Wages serve as a guarantee for the survival of fishermen so that boat owners must provide wages in accordance with their work and fishermen must work according to the agreement. The problem occurs if there is no written work agreement regarding the determination of wages, so that if the policy in work activities is fully controlled by the handler, the handler may act fraudulently in setting wages and also in taking an action such as unilaterally terminating the job without the ship owner’s knowledge. The purpose of this study is to determine the feasibility and fairness in determining the wages of fishing trawlers in Kuala Langsa and to find out the views in Islamic Business Ethics. This type of research is a field study (field research) with descriptive qualitative research methods. Primary data were obtained from interviews with boat owners and fishermen in 5 trawler businesses in Kuala Langsa, while secondary data were obtained through books, scientific papers and documents used to answer problems in research. The researcher concludes that the determination of wages for fishing trawlers in Kuala Langsa is not against Islamic Business Ethics because there is willingness from each party and the fish income obtained is also calculated in a transparent manner. In this case, the fishermen don’t feel wronged because each party receives a legal wage according to the level of their work without being wrongful to the other and the rights and obligations of each party (boat owners and fishermans) have been fulfilled